Rozwiąż układ równań liniowych przez podstawienie:
![Rozwiąż Układ Równań Liniowych Przez Podstawienie class=](https://pl-static.z-dn.net/files/d04/6940d37194e65450a426b5c149689eca.jpg)
Odpowiedź:
4(3x - 1/2) - 5(y + 1/2) = 9
- 2x - 5(y - 2 i 1/2) = - 9y + 11/2
12x - 4/2 - 5y - 5/2 = 9
- 2x - 5y -5(- 5/2) = - 9y + 11/2
12x - 2 - 5y - 2 i 1/2 = 9
- 2x - 5y + 25/2 = - 9y + 11/2
12x - 5y - 4 i 1/2 = 9
- 2x - 5y + 9y = 11/2 - 25/2
12x - 5y = 9 + 4 i 1/2
-2x + 4y = - 14/2
12x - 5y = 13 i 1/2
- 2x + 4y = - 7 /*(-6)
12x - 5y = 13 i 1/2
12x - 24y = 42
12x = 13 i 1/2 + 5y
(13 i 1/2 + 5y) - 24y = 42
12x = 13 i 1/2 + 5y
13 i 1/2 + 5y - 24y = 42
12x = 13 i 1/2 + 5y
5y - 24y = 42 - 13 i 1/2
12x = 13 i 1/2 + 5y
- 19y = 28 i 1/2
12x = 13 i 1/2 + 5y
y = 57/2 : (-19)
12x = 13 i 1/2 + 5y
y = 57/2 * (-1/19)
12x = 13 i 1/2 + 5y
y= 3/2 * (-1/1)
12x = 13 i 1/2 + 5y
y= - 3/2
12x = 13 i 1/2 + 5*(-3/2)
y = - 1 i 1/2
12x = 13 i 1/2 - 15/2
y= - 1 i 1/2
12x= 13 i 1/2 - 7 i 1/2
y= - 1 i 1/2
12x= 6
y = - 1 i 1/2
x= 6 : 12
y= - 1 i 1/2
x= 6/12
y = - 1 i 1/2
x= 1/2
y = - 1 i 1/2
spr.
4(3x - 1/2) - 5(y + 1/2) = 9
L= 4(3x - 1/2) - 5(y + 1/2) = 4(3*1/2 - 1/2) - 5(- 1 i 1/2 + 1/2) =
= 4(3/2 - 1/2) - 5(-1) = 4*2/2 + 5= 4 * 1 + 5= 4 + 5= 9
P= 9
9=9
L=P
Szczegółowe wyjaśnienie: